Stateless Citizenship The Palestinian-Arab Citizens of Israel - Molavi, Shourideh C. (Brill, 2013)
Far from integration into the Israeli incorporation regime, Palestinians inside the state are today placed in a paradoxical situation where, as Arab citizens of a Jewish state, they are both inside and outside, host and guest, citizen and stateless. Through the paradigm of stateless citizenship, Shourideh C. Molavi examines the dynamics of exclusion of Palestinian citizens and analytically frames the mechanisms through which their statelessness is maintained. With this she centres our analytical gaze on the paradox that it is through the actual provision of Israeli citizenship that Palestinians are deemed stateless. Molavi critically engages with the liberal variant of Zionist thought, and deconstructs discourse around minority rights and liberal citizenship in the context of Israel's racialized ideological and political makeup.
Description based on print version record.
KU Select 2017: Backlist Collection
Keywords: Political Science / Civics & Citizenship; Social Science / Sociology; Social sciences; Electronic books